Intensification with pegylated interferon during treatment with tenofovir in HIV–hepatitis B virus co‐infected patients. Issue 12 (3rd August 2016) - Boyd, A.; Piroth, L.; Maylin, S.; Maynard‐Muet, M.; Lebossé, F.; Bouix, C.; Lascoux‐Combe, C.; Mahjoub, N.; Girard, P.‐M.; Delaugerre, C.; Carrat, F.; Lacombe, K.; et al.
Summary: In hepatitis B "e" antigen (HBeAg) positive patients with hepatitis B virus (HBV) mono‐infection, intensification of nucleos(t)ide analogue treatment with pegylated interferon (PegIFN) could help induce higher HBeAg seroclearance rates. Our aim was to determine the long‐term effect of adding PegIFN to tenofovir (TDF)‐containing antiretroviral therapy on seroclearance in HBeAg‐positive patients co‐infected with the human immunodeficiency virus (HIV) and HBV. In this prospective matched cohort study, 46 patients with 1‐year PegIFN intensification during TDF‐containing antiretroviral therapy (TDF+PegIFN) were matched 1:1 to controls undergoing TDF without PegIFN (TDF) using a time‐dependent propensity score based on age, CD4+ count and liver cirrhosis status. Kinetics of HBeAg quantification (qHBeAg) and hepatitis B surface antigen quantification (qHBsAg) were estimated using mixed‐effect linear regression and time to HBeAg seroclearance or HBsAg seroclearance was modelled using proportional hazards regression. At baseline, previous TDF exposure was a median 39.8 months (IQR=21.4–59.4) and median qHBeAg and qHBsAg levels were 6.9 PEIU/mL and 3.72 log10 IU/mL, respectively ( P >.5 between groups). Median follow‐up was 33.4 months (IQR=19.0–36.3). During intensification, faster average declines of qHBeAg (−0.066 vs −0.027 PEIU/mL/month, P =.001) and qHBsAg (−0.049 vs −0.026 log10 IU/mL/month, P =.09) were observed in patients undergoing TDF+PegIFN vs TDF, respectively. After intensification, qHBeAg and qHBsAg decline was no different between groups ( P =.7 and P =.9, respectively). Overall, no differences were observed in HBeAg seroclearance (TDF+PegIFN=13.2 vs TDF=12.6/100 person·years, P =.5) or HBsAg seroclearance rates (TDF+PegIFN=1.8 vs TDF=1.3/100 person·years, P =.7). In conclusion, PegIFN intensification in HBeAg‐positive co‐infected patients did not lead to increased rates of HBeAg or HBsAg clearance, despite faster declines of antigen levels while on PegIFN.